¿Puede el sujeto moderno ponerse de rodillas? Observaciones a Javier Gomá. - Choza, Jacinto (THÉMATA. Revista de Filosofía, 2013)
¿Puede el sujeto moderno ponerse de rodillas? Observaciones a Javier Gomá.